Oil and Insurgency in the Niger Delta Managing the Complex Politics of Petroviolence - Obi, Cyril; Rustad, Siri Aas (Africa Now, 2011)
The recent escalation in the violent conflict in the Niger Delta has brought the region to the forefront of international energy and security concerns. This book analyses the causes, dynamics and politics underpinning oil-related violence in the Niger Delta region of Nigeria. It focuses on the drivers of the conflict, as well as the ways the crises spawned by the political economy of oil and contradictions within Nigeria's ethnic politics have contributed to the morphing of initially poorly coordinated, largely non-violent protests into a pan-Delta insurgency. Approaching the issue from a number of perspectives, the book offers the most up-to-date and comprehensive analysis available of the varied dimensions of the conflict. Combining empirically-based and analytic chapters, it attempts to explain the causes of the escalation in violence, the various actors, levels and dynamics involved, and the policy challenges faced with regard to conflict management/resolution and the options for peace. It also examines the role of oil as a commodity of global strategic significance, addressing the relationship between oil, energy security and development in the Niger Delta.